THE UNDERTAKING CONTRACT AS REGULATED BY THE NEW CIVIL CODE - STANCIU D. CĂRPENARU (Challenges of the Knowledge Society)
The present paper hopes to share a small but comprehensive analysis of the undertaking contract. This type of contract was scarcely regulated by the old Civil Code. Nowadays, the New Civil Code has dedicated a section especially for the undertaking contract. The importance of this paper resides not only in the theoretical aspects but also in the practical perspective that it is hoped to be laid down. In the continuously developing world, despite the economic difficulties in the last years, enterprises and undertakings have continued to be a part of everyday life, and business still strive to maximize profits from this types of contracts.